The Impact of Peripheral Nerve Stimulation on Disability and Depression. Issue 3 (30th October 2015) - Ramineni, Tina; Prusik, Julia; De La Cruz, Priscilla; Gee, Lucy; Kumar, Vignessh; Wilock, Meghan E.; Haller, Jessica; Fama, Chris; Patel, Samik; Pilitsis, Julie G.
Abstract : Background: Peripheral nerve stimulation (PNS) of the named nerves of the head has been shown to be effective in reducing pain levels in patients with chronic pain refractory to other treatments. However, the impact of cranial PNS on depression and disability has not been well documented. Objectives: We prospectively examine the impact of PNS on quality of life via validated survey scores which assess symptoms of depression and daily functional capacities within patients. Methods: Patients who underwent permanent PNS implantation completed five validated questionnaires: Oswestry Disability Index (ODI), the Beck's Depression Inventory (BDI), the Pain Catastrophizing Scale (PCS), McGill Pain Questionnaire (MPQ), and the visual analog scale (VAS) score. These were completed at baseline, six months, and one year to assess changes in functioning levels. Results were analyzed via repeated measures ANOVA and bivariate analysis. Results: Compared with baseline, at six months patients showed significantly less depression on BDI ( F = 7.9, p = 0.021), and at one year, a significant decrease in disability was observed on the ODI (F = 6.1, p = 0.036). At both six months and one year, patients showed a significant decrease in pain on VAS ( F = 16.5, p = 0.012). We noted a trend for ODI to correlate with BDI at six months ( R = 0.616, p = 0.077). Discussion: Our prospective data show PNS to be an effective modality in improving overall life quality by limiting depression and disability as well as pain.